Smart fire notification system - Yaakob, Mohamad Haafidz; Ab Rahman, Azmanirah; Yusop, Azli (Penerbit UTHM, 2020)
The installation cost of fire alarm system are high, therefore many premises unable to install in their premises. Other than that the alarms system used nowadays will only alert people inside the building by siren. Therefore the purpose of the project is to develop a smart fire notification system with low cost and will provide alert system with siren and at the same time will provide twitter notifications for authorities and local residents when fire is occur. The objectives of the project are to develop the smart fire notification prototype, to analyse the sensitivity of the fire detector and to test the functionality of the smart fire notification system. This system can detect fire by two indicator which are heat and smoke. The development process of the smart fire notification system is based on design thinking model that contains five phases namely empathize, define, ideate, prototype and test. The early design of this project was developed using Sketchup software to design a two-storey house model, whereas the development of a hardware using the Fritzing and Arduino IDE software. PushingBox is used to send notifications to twitter when the system detects a fire. Overall, the developed system works well and achieves the objectives.